MANAJEMEN PENYALURAN ZAKAT FITRAH DI KALIMANTAN TENGAH (Studi Kasus di Sukamara, Kotawaringin Timur, Palangka Raya, dan Barito Selatan) - Fitaloka, Diva; Ahmidi; Jamilah; Ali Murtadho; Luqman Hakim (LPPM-IAI BATAM, 2025)
Abstract mustahik. Furthermore, current data indicate the existence of zakat management institutions operating without official authorization, posing risks of misuse of religious social funds. Therefore, optimizing the zakat fitrah management system through enhanced inter-institutional coordination, digital technology utilization, and public education is imperative to ensure more effective and impactful zakat distribution. Zakat fitrah is a religious obligation for every Muslim who possesses sufficient wealth, functioning primarily as an instrument of economic redistribution and spiritual purification prior to the Eid al-Fitr celebration. The effectiveness of zakat fitrah distribution management is a crucial factor in ensuring accurate and timely allocation to eligible recipients (mustahik). This study aims to analyze the zakat fitrah distribution system in four selected regions of Central Kalimantan: Sukamara, Kotawaringin Timur, Palangka Raya, and Barito Selatan. The research employs a qualitative approach, utilizing in-depth interviews and direct observation as primary data collection techniques. In addition, a normative juridical method is applied to examine relevant regulations governing zakat distribution and the authority of managing institutions. The findings reveal that zakat fitrah distribution in these areas is generally conducted through mosques, zakat institutions, and local government bodies. However, several challenges persist, including unequal distribution, limited use of information technology for zakat recordkeeping, and inadequate oversight in the allocation process to mustahik. The study also highlights the continued operation of unauthorized zakat institutions, as reported by the Indonesian Ministry of Religious Affairs in 2023, which potentially undermines transparency and accountability in zakat fitrah management. Moreover, the presence of unlicensed zakat managers poses a risk of misuse of religious social funds. Therefore, optimizing the zakat fitrah management system through strengthened inter-institutional coordination, digital technology adoption, and enhanced public literacy on zakat is essential to ensure a more effective and sustainable distribution. Kata Kunci: Management, Distribution, Zakat. Abstrak Zakat fitrah merupakan kewajiban bagi setiap Muslim yang memiliki kecukupan harta, dengan fungsi utama sebagai instrumen pemerataan ekonomi dan penyucian jiwa menjelang Hari Raya Idul Fitri. Efektivitas manajemen penyaluran zakat fitrah menjadi faktor krusial dalam memastikan distribusi yang tepat sasaran dan tepat waktu kepada para mustahik. Penelitian ini bertujuan untuk menganalisis sistem penyaluran zakat fitrah di empat daerah di Kalimantan Tengah, yaitu Sukamara, Kotawaringin Timur, Palangka Raya, dan Barito Selatan. Metode yang digunakan adalah pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara mendalam dan observasi langsung, serta dilengkapi dengan pendekatan yuridis normatif untuk menelaah regulasi terkait penyaluran zakat dan otoritas lembaga pengelolanya. Hasil penelitian menunjukkan bahwa penyaluran zakat fitrah di wilayah tersebut dilakukan melalui masjid, lembaga zakat, dan pemerintah daerah. Namun, sejumlah tantangan masih dihadapi, seperti pendistribusian yang belum merata, minimnya pemanfaatan teknologi informasi dalam pencatatan zakat, serta lemahnya pengawasan terhadap penyaluran kepada mustahik. Penelitian ini juga menyoroti keberadaan lembaga zakat ilegal yang masih aktif beroperasi, sebagaimana dirilis Kementerian Agama RI pada tahun 2023, yang berpotensi memengaruhi transparansi dan akuntabilitas dalam pengelolaan zakat fitrah. Selain itu, ditemukan adanya lembaga pengelola zakat yang beroperasi tanpa izin resmi, yang berpotensi menimbulkan penyalahgunaan dana sosial keagamaan. Oleh karena itu, diperlukan optimalisasi sistem pengelolaan zakat fitrah melalui penguatan koordinasi antarlembaga, pemanfaatan teknologi digital, serta peningkatan literasi zakat kepada masyarakat guna mendorong penyaluran zakat yang lebih efektif dan berkelanjutan. Kata Kunci: Pengelola, Distribusi, Zakat.